2015
DOI: 10.1016/j.jaci.2015.06.001
|View full text |Cite|
|
Sign up to set email alerts
|

Consensus communication on early peanut introduction and the prevention of peanut allergy in high-risk infants

Abstract: The purpose of this brief communication is to highlight emerging evidence to existing guidelines regarding potential benefits of supporting early, rather than delayed, peanut introduction during the period of complementary food introduction in infants. This document should be considered as interim guidance based on consensus among the following organizations: American Academy of Allergy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(76 citation statements)
references
References 15 publications
(21 reference statements)
3
70
0
Order By: Relevance
“…These findings are reassuring in the context of new consensus communications to feed peanut early to high-risk, atopic infants. (6-8) Interestingly, we found that despite peanut consumers making different food choices to peanut avoiders, both achieved nutritional priorities of energy and protein homeostasis. This occurs through a trade-off between carbohydrate and fat contributions to energy intake.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These findings are reassuring in the context of new consensus communications to feed peanut early to high-risk, atopic infants. (6-8) Interestingly, we found that despite peanut consumers making different food choices to peanut avoiders, both achieved nutritional priorities of energy and protein homeostasis. This occurs through a trade-off between carbohydrate and fat contributions to energy intake.…”
Section: Discussionmentioning
confidence: 85%
“…However, clinicians should still emphasize that whole peanuts and chunks of peanut butter are a choking hazard in young children and should not be consumed before 5 years of age. (6-8,13)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant protective effect against rhinitis was seen only in the validation cohort and is difficult to interpret, as this cohort’s rhinitis definition does not differentiate between atopic and non-atopic symptoms. With the publication of the LEAP study(46) and the Consensus statement on peanut introduction(47) changes in the timing of introduction of solid foods is recommended, particularly the introduction of solid foods and peanuts before 6 months of age. This paper is reassuring in the fact that 6 months exclusive breasting does not seem to be important for allergy prevention.…”
Section: Discussionmentioning
confidence: 99%
“…They found that peanut consumption was effective in reducing the prevalence of peanut allergy both in children who were not sensitized to peanuts (primary prevention) and in those who were sensitized (secondary prevention) in comparison with controls. Consequently, a consensus communication [4] recommended early introduction of peanut to prevent peanut allergy in children at risk. However, the term early seems to be inappropriate and it may be misinterpreted, since findings by Du Toit et al [1] do not imply that current weaning plan should be modified [5].…”
Section: Reviewmentioning
confidence: 99%